2018
DOI: 10.1016/j.cbpra.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Guided Recovery: An Interpretative Phenomenological Analysis of Service Users’ Experiences of Guided Self-Help for Bulimic and Binge Eating Disorders

Abstract: The efficacy of Cognitive Behavioral Therapy-based Guided Self-Help for mild to moderate bulimia and binge eating disorders has been well supported. However, limited research has explored in-depth individual experiences of this treatment approach. In depth semi-structured interviews were conducted with four individuals who had completed Cognitive Behavioral Therapy based Guided Self Help (CBT-GSH) for bulimic or binge eating disorders. The interviews were transcribed verbatim and subsequently analysed using In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…In the second conceptualization, despite accessibility and flexibility being noted as advantages, they were not the main reasons that attracted the participants. GSH as a “second‐best” option was noted in several papers (e.g., McClay et al (); Plateau et al ()), such as “there isn't much help out there…a long waiting list…” (McClay et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the second conceptualization, despite accessibility and flexibility being noted as advantages, they were not the main reasons that attracted the participants. GSH as a “second‐best” option was noted in several papers (e.g., McClay et al (); Plateau et al ()), such as “there isn't much help out there…a long waiting list…” (McClay et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the study by Traviss et al () where some self‐help guides were interviewed, one of them observed that participants with more positive outcomes were those who were “willing to take more responsibility.” Leung et al () also included ideas about “taking control” instead of “letting ED control you,” and “…[the program] makes me more determined to fix myself.” It is clear that engagement with the program was seen as being effortful. As illustrated by Plateau et al (), participants used words such as “allow,” “try,” “have to” to describe the process. In this respect, computer‐based GSH was seen as more effective than book‐based GSH because it did not allow unstructured browsing (Sanchez‐Ortiz et al ()): “it took you through step by step… the computer can do much more than a book… you just skip through [in a book] whereas if it's on the computer you have to go step by step and then you can't move on until you've thought about it and done it so that, I think was a lot more effective.”…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations